1997
DOI: 10.1074/jbc.272.42.26388
|View full text |Cite
|
Sign up to set email alerts
|

A Region of the β Subunit of the Interferon α Receptor Different from Box 1 Interacts with Jak1 and Is Sufficient to Activate the Jak-Stat Pathway and Induce an Antiviral State

Abstract: Type I interferons (IFNs) 1 bind to a multimeric receptor (type I IFN-R, IFN␣R, or IFN␣␤R) composed of at least two subunits designated as ␣ (1-5), and ␤ (6, 7). The IFN␣/␤R cDNA (8) corresponds to the short form of the ␤ subunit (␤ S ), whereas cDNAs for the long form (␤ L ) have been recently isolated by two different groups (9, 10). Transcripts and mature proteins for both ␤ S and ␤ L are found in most cell lines, although there is a large excess of ␤ L protein when compared with ␤ S .2 Lutfalla et al. (10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
80
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 35 publications
2
80
0
1
Order By: Relevance
“…For example, Tyk2 interacts with a domain of IFN-␣R␣, the ␣-chain of the IFN-␣R (also designated as IFNAR1 or IFN-␣R1), which has only distant homology with the box 1 or box 2 motifs (25,26). Jak1 is activated by multichain receptors such as the IL-6 group of cytokines (IL-6, leukemia inhibitory factor, ciliary neurotrophic factor, oncostatin M), IFN-␣, IFN-␥, IL-10, and those cytokine receptors that belong to the IL-2 family (IL-2, IL-4, IL-7, IL-9, and IL-15) (19,20,(27)(28)(29)(30)(31)(32)(33). The Jak1 binding site on cytokine receptors has been explored in only a few cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tyk2 interacts with a domain of IFN-␣R␣, the ␣-chain of the IFN-␣R (also designated as IFNAR1 or IFN-␣R1), which has only distant homology with the box 1 or box 2 motifs (25,26). Jak1 is activated by multichain receptors such as the IL-6 group of cytokines (IL-6, leukemia inhibitory factor, ciliary neurotrophic factor, oncostatin M), IFN-␣, IFN-␥, IL-10, and those cytokine receptors that belong to the IL-2 family (IL-2, IL-4, IL-7, IL-9, and IL-15) (19,20,(27)(28)(29)(30)(31)(32)(33). The Jak1 binding site on cytokine receptors has been explored in only a few cases.…”
mentioning
confidence: 99%
“…For instance, mutational analysis of the L 267 PKS 270 (leucine, proline, lysine, serine) motif of the ␣-chain of the IFN-␥R␣ (also designated as IFNGR1 or IFN-␥R1), which has only very distant similarity with the box 1, revealed that only Pro 268 was important for Jak1 binding (20). In contrast, the main Jak1 binding site on the IFN-␣R␤ L (also designated as IFNAR2 or IFN-␣R2) chain is clearly different from the box 1 (29) and more distant from the transmembrane region than the Jak1 site described for the IFN-␥R␣. In the case of the IL-2R␤ chain, a sequence with some similarity to the box 1 and a more distal region appear to be important for Jak1 binding (34,35).…”
mentioning
confidence: 99%
“…[19][20][21][22] This receptor, on binding these type I IFNs, activates the Jak-STAT signaling cascade, to upregulate transcription of an array of cellular genes. [23][24][25] These IFNs have important effects on the immune system: they alter expression, activation, and localization of many cellular proteins, including MHC-I and -II, and TNFa, that activate and execute antiviral T and NK cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…The ␣ and ␤ subunits of the type I IFN-R associate with protein tyrosine kinases of the Jak family (4,8,18). The ␣ subunit interacts with Tyk2 (4,19,20) while the cytoplasmic domain of the ␤ L contains a docking site for Jak1 (18).…”
mentioning
confidence: 99%
“…Expression of the human ␣ and long form of the ␤ chain (␤ L ) subunits in mouse L-929 cells fully reconstitutes the activation of the Jak-Stat pathway and the induction of an antiviral state in response to HuIFN␣2 and HuIFN␤ (9). Furthermore, only the first 82 amino acids of the cytoplasmic domain of the ␤ L chain are required to activate the Jak-Stat pathway and induce the antiviral effect in response to IFN␣2 (18).The ␣ and ␤ subunits of the type I IFN-R associate with protein tyrosine kinases of the Jak family (4,8,18). The ␣ subunit interacts with Tyk2 (4,19,20) while the cytoplasmic domain of the ␤ L contains a docking site for Jak1 (18).…”
mentioning
confidence: 99%